Amplified Spontaneous Emission from Perovskite Quantum Dots Inside a Transparent Glass. Issue 6 (29th January 2022) - Tian, Xiangling; Wei, Rongfei; Ma, Zhijun; Qiu, Jianrong
Abstract: The diverse optoelectronics systems can provide interesting design inspiration for photonics devices, ranging from optical modulators to light‐emitting displays. With the increasing applications and requirements of optical interconnect in complex environments, an essential operation is increasingly being pursued to exploit the consolidation of various merits of basic components. Here, an optical gain from monodisperse CsPbBr3 quantum dots crystallized in a selected transparent glass is revealed. The threshold of amplified spontaneous emission increases from 7.4 to 100.4 µJ cm −2 with the temperature from 78 K to room temperature, accompanied with a high gain coefficient of 627.9 cm −1 . A small fluctuation of the lifetime (≈10.5%) with temperature and the photostability (>12 h) with the excitation of femtosecond laser indicates the robustness of the crystallized CsPbBr3 quantum dots in the transparent glass. These demonstrations present a deep understanding of the optical gain in the composite of metal halide perovskites and transparent glass and pave a path for the potential applications of CsPbBr3 ‐based glass–ceramics as a gain medium for coherent light sources including laser/incoherent diode, fiber laser as well as optical amplifier chips. Abstract : Amplified spontaneous emission along with a gain coefficient as high as 627.9 cm −1 in a heat‐treated glass including cesium lead bromide quantum dots with a temperature from 78 to 300 K is detected. Importantly, the quantum dots dispersed in the transparent glass show robustness with the temperature and the excitation of the laser pulse.